Maternal perceptions of breastfeeding and infant nutrition among a select group of Maasai women - Marie Dietrich Leurer; Pammla Petrucka; Manjale Msafiri (BMC, 2019)
Abstract Background Adverse health outcomes are higher among Maasai children in the Ngorongoro Conservation Area compared to other co-located ethnic groups and regions of Tanzania. The Mama Kwanza Socioeconomic Health Initiative, a Canadian-Tanzanian partnership delivering healthcare at clinics in this region, gathered perceptions of mothers regarding breastfeeding and infant nutrition in order to inform culturally sensitive, realistic, and effective health promotion efforts. Methods A qualitative description approach was used in interviewing 30 Maasai mothers of infants zero to six months of age to explore their infant feeding practices, beliefs, knowledge, and recommendations to support breastfeeding. A local research team was trained to conduct and transcribe the interviews and assist with data interpretation. Qualitative content analysis was used in analyzing the interview transcripts. Results Lactation is universal in this culture with all the mothers planning to breastfeed for at least one year and most having initiated breastfeeding within one hour of birth. Lactation skills and knowledge are passed down intergenerationally from the elder women. None of the infants less than six months were exclusively breastfed, with a variety of liquid and semi-solid supplements given. Mothers perceived their milk alone was nutritionally insufficient with maternal dietary deficiencies cited as a factor. Conclusions While there is a strong breastfeeding culture among the Maasai in Ngorongoro, intersectoral efforts are required to provide culturally respectful health education on the benefits of exclusive breastfeeding and to ensure the maternal dietary adequacy required to achieve this goal. The findings reinforce the importance of international health projects adapting health promotion initiatives to local realities and beliefs in efforts to improve maternal child health.